The complete mitochondrial genome of Cheilinus trilobatus (Perciformes: Labridae) - Teng Wang; Yupei Li; Qin Ma; Yong Liu; Yayuan Xiao; Peng Wu; Lin Lin; Chunhou Li (Mitochondrial DNA. Part B. Resources, 2023)
Cheilinus trilobatus Lacépède, 1801 is a species of genus Cheilinus. In this study, we sequenced the complete mitochondrion genome of C. trilobatus. The mitochondrial genome was 17,292 bp, consisting of 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and one non-coding control region (D-loop). The nucleotide composition was 27.31% A, 25.1% T, 17.23% G, and 30.36% C. Phylogenetic analysis suggested that C. trilobatus was closely related to Cheilinus oxycephalus. The complete mitogenome of C. trilobatus provided basic data for the genetic diversity conservation of this species.